2006
DOI: 10.1203/01.pdr.0000219120.92049.b3
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Suppresses Expression of Nuclear Factor-kappaB in the Cells of Tracheobronchial Lavage Fluid in Premature Neonates with Respiratory Distress

Abstract: Nuclear Factor-kappaB (NF-kappaB) plays a central role in regulating the key mediators of inflammation involved in acute lung injury. The anti-inflammatory effect of steroids by suppressing pro-inflammatory cytokines may be mediated by inhibition of transcription factor NF-kappaB. The objective of this study was to determine the effect of glucocorticoid therapy on the expression of NF-kappaB in the cells of tracheobronchial lavage fluid (TBLF) in premature neonates with respiratory distress. Nineteen premature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
(36 reference statements)
0
35
0
Order By: Relevance
“…However, the predominant cells in TA are neutrophils and alveolar macrophages. We, and others, have shown that NF-B is localized and activated in both the neutrophils and alveolar macrophages in TA obtained from preterm infants (8,15).…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…However, the predominant cells in TA are neutrophils and alveolar macrophages. We, and others, have shown that NF-B is localized and activated in both the neutrophils and alveolar macrophages in TA obtained from preterm infants (8,15).…”
mentioning
confidence: 57%
“…We recently reported that dexamethasone therapy suppresses the activation of NF-B in pulmonary leukocytes from premature infants (8). Dexamethasone therapy not only suppressed the expression of NF-B but also decreased the concentrations of pro-inflammatory mediators in ventilated preterm infants.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…25 In addition, HMGB1 has been shown to act through NF-kB, 4,26 glucocorticoids are known to inhibit the NF-kB signaling system, 27 and Dex has been shown to suppress NF-kB expression in TA cells obtained from VPI. 28 Hence, we had expected to observe a decrease in HMGB1 levels in response to Dex treatment. This, however, did not turn out to be true.…”
mentioning
confidence: 99%
“…Thus, preterm infants with very severe respiratory failure are still being treated with corticosteroids, despite the awareness of the negative effects on neurodevelopment (8,27,28). The mechanisms for the improvement in lung function are not fully elucidated, and possibly include a down-regulation of lung inflammation (29) and a reduction of lung water (30,31). Scanty information exists on the role of DEXA on surfactant metabolism in general and more so in human infants.…”
Section: Discussionmentioning
confidence: 99%